Machiavellianism and Executive Functioning in Patients with Delusional Disorder. - Brüne, Martin; Basilowski, Miriam; Bömmer, Isabel; Juckel, Georg; Assion, Hans-Jörg (Psychological Reports, 2010)
Previous research has demonstrated that patients with Delusional Disorder are impaired in executive functioning that affects performance on social cognitive tasks. In patients with Parkinson's disease, poor executive control induces an increase in “Machiavellianism,” a term that refers to opportunistic behaviors that aim at exploiting and manipulating others. Accordingly, the association between Machiavellianism in Delusional Disorder and executive functioning deficits was examined. Machiavellianism and executive functioning were measured in 22 patients with Delusional Disorder and compared with a group of 22 healthy controls matched for sex, (premorbid) intelligence, and education. Patients and controls did not differ regarding Machiavellianism scores, education level, or intelligence. However, patients with Delusional Disorder performed more poorly on an executive functioning task. Impaired executive functioning was associated with greater Machiavellianism, particularly cynical views on human nature, but not with intelligence or illness duration. Similar to findings in patients with Parkinson's disease, Machiavellianism in Delusional Disorder was associated with poorer executive functioning. This finding indicates that frontal lobe dysfunction may influence interpersonal attitudes and personality in Delusional Disorder.